KONFLIK DAN RESOLUSINYA DALAM PERSPEKTIF ISLAM - Akhmad Rifa’i (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
Al-Quran as a source of Islamic law have been explained systematically, that the human condition will be conflict in the interaction between each other. In verse of al-Baqara (2:30), even before the creation explains Adam (first human), Angel says that man is only to conflict and corruption on the earth. Here is not inevitable, the Qur’an has so far explained the conflict before humans existed. Al-Quran itself explains also that the conflicts that exist in humans can be resolved. The Qur’an has a draft resolution. Explanation verse of An-Nisa (4:35) and a verse of al-Hujurat (49:09) provide evidence that Al-Quran is concerned with the conflict. Conflict resolution offered by the Qur’an when it conflicts with a person or party outside, Hakam must be able to reconcile the conflicting parties. Hakam or arbitrator in the science of conflict resolution is often called a mediator in the mediation system. Conflict and resolution in the perspective of Islam (the Qur’an), so badly needed in answering the question of existing conflicts in human life.